Postpartum Acute Coronary Syndrome Due to Intramural Hematoma and Coronary Artery Dissection - Julià, Ignasi; Tauron, Manel; Muñoz-Guijosa, Christian (The Thoracic and Cardiovascular Surgeon, 2013)
A 38-year-old woman presented with acute coronary syndrome 9 days postpartum. Coronary catheterization showed an intramural hematoma of the left main artery (LM) and the left anterior descending artery (LAD). During angiography, dissection of the LM, with involvement of the LAD and circumflex artery occurred. The patient presented unstable hemodynamic status. After resuscitation, intra-aortic balloon pump was inserted. The patient underwent two-vessel off-pump surgical revascularization. She was discharged 10 days later.
Keywords: coronary artery; coronary percutaneous interventions; coronary artery bypass grafting; complications